Studi Pemeriksaan Sedimen Urine berdasarkan Karakteristik Pada Penikmat Kopi di Asrama Kiwal Brawijaya Surabaya - Pipit Festy Wiliyanarti; Jilan Atrasina; Ellies Tunjung Sari Maulidiyanti (Universitas Muhammadiyah Surabaya, 2021)
Coffee is a psychostimulant drink which can provide good benefits for the body if consumed in moderation. However, one of the effects in excessive coffee consumption over a long period of time that is not accompanied by adequate fluid intake is in fact able to affect sedimentation in urine. The caffeine content which has a lot of particles can cause the kidneys to be unable to reabsorb it. Therefore, it is excreted along with the urine and it causes the urine to be more concentrated. This causes increased sedimentation in the urine. The purpose determined the description of urine sediment examination on coffee connoisseurs in Asrama Kiwal in Brawijaya of Surabaya. The research type used descriptive research with a research sample of 40 people taken by purposive sampling. The results showed that the description of urine sediment examination on coffee connoisseurs at Asrama Kiwal in Brawijaya of Surabaya that 12 people (30%) had normal urine sediment and 28 people (70%) had abnormal urine sediment. Based on the characteristics of the respondents, the presence of abnormal urine sediment was found in the age category 30 years as many as 26 people (76%) with a frequency of coffee consumption > 3 times per day as many as 14 people (35%) in a series of coffee consumption for > 10 years as many as 27 people ( 67.5%) and the frequency of consumption of mineral water 2 litters per day as many as 24 people (60%). The conclusion of this study was that most of the coffee connoisseurs in Asrama Kiwal Brawijaya of Surabaya that experienced abnormal urine sedimentation.Keywords: Coffee, Urine Sediment